The effect of endodontic irrigants on the microtensile bond strength of different dentin adhesives - Dikmen, Benin; Tarım, Berna (Medknow Publications & Media Pvt Ltd, 2018)
Objectives: The aim of this study was to determine the influence of irrigants on bond strength of adhesive systems. Materials and Methods: Superficial dentin surfaces of 60 extracted molars were divided into 15 groups, according to irrigants and adhesives. In the control groups, surfaces were irrigated with distilled water. In experimental groups, sodium hypochlorite (NaOCl), ethylenediaminetetraacetic acid (EDTA) + NaOCl, chlorhexidine (CHX), and NaOCl + sodium ascorbate were used as irrigants. Resin composites were then built up using Single Bond, Clearfil SE Bond, and Xeno 3 as adhesives. The microtensile bond strength of groups was determined. Data were statistically analyzed by two-way analysis of variance (ANOVA), one-way ANOVA, and the Bonferroni test. Results: NaOCl reduced bond strength of Single Bond and Clearfil SE Bond (P <0.01). For all adhesive systems, EDTA + NaOCl-treated groups exhibited lower bond strength than control groups (P <0.01). CHX decreased bond strength of Single Bond (P <0.01). Application of sodium ascorbate improved compromised bond strength to NaOCl-treated dentin (P <0.01). Conclusion: Different irrigants had several effects on bonding of different adhesives. Sodium ascorbate after NaOCl could restore compromised bond strengths.
WOS: 000427371000005
PubMed ID: 29519974
Keywords: Adhesive; Antioxidant; Composite; Irrigation; Microtensile Bond Strength